Study on deformation and failure characteristics of overlying strata with thick loose layers and thin bedrock based on Hoek-Brown criterion - Li Quansheng; Xu Zhuhe; Zhang Yong; He Wenrui (矿业科学学报, 2019)
The mechanics parameters of rock mass in Wulanmulun mine are determined on the basis of the experimental data measured in the laboratory and applied Hoek-Brown criterion in this paper.On this basis the failure characteristics of overlying strata caused by coal mining are studied through FLAC3D simulation software.The research results show that:① The overlying strata under shallow burial depth until surface has been destroyed, and the skewness subsidence basin is formed on the surface.The maximum subsidence is 2.1m, and the subsidence rate is 0.6.② The stress-relaxed area and the stress-increased area are formed in a certain range of the surrounding boundary of the mining area.The state presents "external tight internal loosing".The degree of vertical stress concentration in front of coal wall is the highest, and the stress concentration factor is 2.2.There is a pressure arch separately above the coal wall and the open-off cut, but the span, the size of the arch foot and the degree of stress concentration are different.③The height of the caving zone is 18.9 m, and the height of water flowing fractured zone is 62.5 m of 12403 face in Wulanmulun coal mine.